An important rule of logs is a*log b = log b^a.
Thus, 2 (log to the base 5 of )(5x^3) = (log to the base 5 of ) (5x^3)^2, or
(log to the base 5 of ) (25x^6).
Next, (1/3) (log to the base 5 of ) (x^2+6) = (log to the base 5 of ) (x^2+6)^(1/3).
Here, the addition in the middle of the given expression indicates multiplication:
2Log5(5x^3)+1/3log5(x^2+6) = (log to the base 5 of ) { (5x^3)^2 * (x^2+6)^(1/3) }.
Here we've expressed the given log quantity as a single log.
Step-by-step explanation:
By substituting x = 0.4 in equation 7 + (-3x^2)
= 7 - 3 (0.4)^2
First solving o.4^2 as per the rule of BODMAS
= 7- 3 (0.16)
Now multiplying -3 with 0.16
= 7 - 0.48
= 6.52 THIS IS THE ANSWER
The answer to this is 38300 hope this helped
Answer is C
hope this helps!